HVDC TRANSMISSION LINE PROTECTION BASED ON TRANSIENT ENERGY AND TRANSIENT POWER: A SURVEY - Teklu, Henok; Panchal, Amit (International Journal of Engineering Technologies and Management Research, 2018)
As the number of consumers of electricity increases the electric power generated required to serve the consumers increases. Due to the long distance transmission of the generated power the power system becomes complex. That is why HVDC transmission system used for long distance carriage of power. During transmission of HVDC system protection and security of the system is compulsory in order to minimize the overall losses. This review paper discusses the protection of HVDC line based on transient energy and transient power. The fault which is occurred on the system reflected on three main parts of the system. Using modified traveling wave algorithm the transient parameters are determined and the type and location of fault can be detected. The simulation is done using PSCAD/EMTDC, MATLAB/Simulink. Motivation/Background: Due to the complication of a power system, HVDC power transmission system was chosen. But the system needs protection to secure the transportation of the needed amount of power. Method: In this review paper a modified travelling wave algorithm is used to detect the faults. Results: The result from the output of the algorithm shows the transient power and energy came to stability within short time. Conclusions: By detecting the transient power and energy, it can easily be protect the system from severe problem.